The Influence of Blended Learning and Visual, Auditory, Kinesthetic (VAK) Learning Styles on Students' Speaking Skills in Class XI English Language Learning - Khopiya Nida; Yayat Ruhiat; Isti Rusdiyani (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2023)
The aim of this research is to determine the effect of blended learning and visual, auditory, kinesthetic (VAK) learning styles on students' speaking skills when learning English. The research method used is experimental research. The experimental design used was a factorial design, while this research used a non-equivalent control group pre-test. The research results show that: (1) There are differences in the English language skills of students who are taught through blended learning and online learning; (2) There is a reciprocal influence between blended learning and online learning models as well as visual, auditory, kinesthetic (VAK) learning on students' English language skills; (3) There are differences in English language skills between students taught using blended learning and online learning with visual learning; ( 4) There are differences in English language skills between students who are taught through blended learning and online learning techniques, and students who receive auditory learning; and (5) There are differences in English language skills between students taught via blended learning and online learning methods and students with a kinesthetic learning style.